Structural basis of RNA polymerase complexes in African swine fever virus - Guoliang Zhu; Fei Xi; Wuxia Zeng; Yifei Zhao; Weijun Cao; Chen Liu; Fan Yang; Yi Ru; Shuqi Xiao; Shilei Zhang; Huanan Liu; Hong Tian; et al. (Nature Communications)
Abstract African swine fever virus is highly contagious and causes a fatal infectious disease in pigs, resulting in a significant global impact on pork supply. The African swine fever virus RNA polymerase serves as a crucial multifunctional protein complex responsible for genome transcription and regulation. Therefore, it is essential to investigate its structural and functional characteristics for the prevention and control of African swine fever. Here, we determine the structures of endogenous African swine fever virus RNA polymerase in both nucleic acid-free and elongation states. The African swine fever virus RNA polymerase shares similarities with the core of typical RNA polymerases, but possesses a distinct subunit M1249L. Notably, the dynamic binding mode of M1249L with RNA polymerase, along with the C-terminal tail insertion of M1249L in the active center of DNA-RNA scaffold binding, suggests the potential of M1249L to regulate RNA polymerase activity within cells. These results are important for understanding the transcription cycle of the African swine fever virus and for developing antiviral strategies.